Ice hockey injuries: a 4-year prospective study of a Swedish élite ice hockey team. - Pettersson, M (1993)
In this prospective study, we have investigated the incidence of injuries of different severity, types of injury, and mechanisms of injury during ice hockey practice and games. One Swedish élite hockey team was closely observed during four seasons (1986-1990). There were 376 injuries, of which 148 resulted in absence from practice or games. The incidence of injury (injuries associated with later absence) during practice was 2.6 per 1000 player-practice hours and 74.1 per 1000 player-game hours. Nuisance injuries (without any later absence) and minor injuries (absence < 1 week) constituted the vast majority (95.2%) and only 4.8% (18 cases) were classified as moderate or major injuries (absence > 1 week). Of the injuries 85% were caused by trauma and 15% by overuse. Injuries were most often localized to the lower limb (37.8%) and head/face (31.4%). The commonest injuries were contusions, lacerations/wounds, strains and sprains. Most injuries resulted from stick or player contact (predominantly checking). The results are in close agreement with those of a previous investigation of another Swedish élite hockey team covering the years 1982-1985. It should be possible to reduce the number of injuries by stricter enforcement of the hockey rules, especially against stick violations, and a more widespread use of visors.